THE INFLUENCE OF BIBLIOTHERAPY ON HOSPITALIZATION ANXIETY LEVELS IN PRESCHOOL CHILDREN : A LITERATUR REVIEW - Sumartini, Rina; Nursekhah, Ika (Rifapublisher.id, 2025)
Background: Hospitalization can lead to increased anxiety levels in preschool children. Anxiety in preschool children undergoing hospitalization is caused by the environment and healthcare providers. Hospitalization anxiety can be minimized through play, including reading storybooks. The use of books as a therapeutic medium is referred to as bibliotherapy. Objective: The aim of this study is to determine the effect of bibliotherapy on hospitalization anxiety among preschool children. Method: The method used in this study is a literature review. Academic articles were searched online from 2010 to 2023 using the PICO (Population, Intervention, Comparative, Outcome) framework. Five relevant articles were selected after screening. Result: The results of this study indicate that bibliotherapy is effective in reducing hospitalization anxiety levels among preschool children. Conclusion: Based on a literature review of 5 journals on the impact of bibliotherapy on hospitalization anxiety levels in preschool children, it can be concluded that bibliotherapy is effective in reducing hospitalization anxiety levels in preschool children.